Spatial transcriptomic mapping of postnatal mouse uterine development - M. Fairuz B. Jamaluddin; Shafiq M. Syed; Riazuddin Mohammed; Jyoti Goad; Mehedi Hasan; Manish Kumar; Isabella Moore; Prathima B. Nagendra; Naga Veera Srikanth Vallabani; Florence Bartlett; Vimala Anthonydhason; Pradeep S. Tanwar (Proceedings of the National Academy of Sciences, 2026)
Postnatal uterine development requires precise coordination of epithelial differentiation, gland formation, and stromal organization, yet how transcriptional programs are spatially integrated during this process remains poorly understood. Here, we generated a spatially resolved transcriptomic map of the mouse uterus across key postnatal stages from day 3 to day 21 by combining high resolution in situ transcriptomics with histology, proteomics, genetic models, and functional assays. This approach defines the temporal emergence and spatial arrangement of all major uterine cell types and demonstrates that endometrial glands arise from luminal epithelium through progressive transcriptional reprogramming rather than from a prespecified progenitor population. Spatial analysis reveals marked compartmentalization of signaling pathways during adenogenesis. Luminal epithelium is enriched for Wnt ligands and hormone receptors, whereas glandular epithelium engages inhibitory and negative feedback programs that constrain Wnt activity while supporting proliferation and differentiation. Functional genetic studies establish that epithelial canonical Wnt signaling is essential for prepubertal gland establishment and long-term epithelial maintenance but is dispensable for postpartum gland regeneration. Retinoic acid synthesis becomes increasingly concentrated within glands, while hedgehog signaling polarizes into an epithelial to stromal axis during gland morphogenesis. Additional pathways including RTK, Notch, TGFβ, BMP, hypoxia, Hippo, and PI3K-mTOR exhibit distinct spatial biases that collectively shape epithelial identity and tissue maturation. Together, these findings provide a comprehensive spatial framework for uterine gland development and reveal how compartment specific signaling networks coordinate postnatal uterine morphogenesis.